EFFECT OF ETHYL SALICYLIC ACID VAPOUR ON SPROUTING AND ROTS INCIDENCE OF POTATO TUBERS UNDER LONG-TERM STORAGE(a) - Mostafa M; E. Gado (Arab Universities Journal of Agricultural Sciences, 2007)
The effect of exposing of potato tubers cv. Di-amond to ethyl salicylic acid (ES) vapour for dif-ferent doses and different periods of exposing on rots incidence and sprouting of tubers under long term storage was studied. Expose of tubers to high doses of vapour (resulted from evaporation of 0.5 or 1 ml/ liter space) for 6 h led to appear a very strong harmful effect on exposed tubers stored for 4 months. All tubers were decayed, collapsed and severely infected by rot pathogens. Expose of tu-bers to middle dose (0.25 ml/liter space) for 6, 12, 24, or 48 h then stored for 4 months at ambient temperature showed variable effects. Six or 12 h exposing led to slight reduction of rot incidence but it had not effect on sprouting in comparison to non-exposed tubers. On the other hand, exposing, for 24 or 48 h suppressed sprouting completely and reduced to very great extent rots incidence (%). Storage of tubers exposed to 0.25 ml/ liter for 24 h at high relative humidity (~90%) or under cooling (6-8 Cْ ) did not cause any reduction in compound efficiency. Expose of tubers to low dose of ES vapour (0.125 ml/ liter space) for dif-ferent periods showed that exposing for 6 or 12 h led to stimulatory effect on sprouting without ef-fect on rots incidence. Twenty four hours exposing led to decrease rots incidence and sprouting.These results clearly indicated that ES vapour had variable effects on exposed tubers depend upon dose and period of exposing.